2019
DOI: 10.1111/asj.13289
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of maternal origin factors during transition from embryonic diapause to implantation in roe deer

Abstract: The aim was to evaluate in female roe deer: (a) PAG mRNA relative abundance in endometrial uterine tissue for determination of the duration of embryonic diapause, (b) mRNA relative abundance of progesterone, estradiol, and prolactin (P4, E2, and PRL) receptors (PGR, ESR, and PRLR) during diapause and after implantation in the endometrium; (c) concentration of P4, E2, and PRL in the blood, and (d) a noninvasive method of hormone detection by measurement of P4 and E2 concentrations in feces. A total of fifteen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Studies focusing on plasma or endometrial hormone concentrations in the roe deer found little to no changes prior to implantation (Drews et al, 2019; Flint et al, 1994; Hoffmann et al, 1978; Korzekwa et al, 2019; Lambert et al, 2001; Sempéré, 1977; van der Weijden et al, 2019). In addition, corpora lutea remain active during the diapause period (Hoffmann et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on plasma or endometrial hormone concentrations in the roe deer found little to no changes prior to implantation (Drews et al, 2019; Flint et al, 1994; Hoffmann et al, 1978; Korzekwa et al, 2019; Lambert et al, 2001; Sempéré, 1977; van der Weijden et al, 2019). In addition, corpora lutea remain active during the diapause period (Hoffmann et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Anuradha and Krishna [62] demonstrated PRL participation during delayed embryonic development, regulating the progesterone and estradiol levels associated with luteotropic function in Cynopterus sphinx (short-nosed fruit bat). Korzekwa et al [63] showed increased progesterone and PRL serum levels, determined by ELISA and mRNA upregulation of the long PRLr isoform, in endometrial tissue during the switch from diapause to placentation in Capreolus capreolus (Roe deer). According to recent studies, PRLr content quantified by PCR is lower during diapause than during reactivation in Mustela vison (mink), the primary animal model used to evaluate diapause, uterus [64].…”
Section: Diapause: a Stage Of Embryo Development When Pluripotency Is...mentioning
confidence: 99%